(untitled) (American Journal of Islam and Society, 2000)
The anthology, Islam, Gender and Social Change, starts with an introduction by Professor John Esposito, one of the coeditors, and it continues with an overarching chapter "Islam and Gender: Dilemmas in the Changing Arab World" by the other coeditor, Professor Yvonne Yazbeck Haddad. The introduction gives a short survey of gender issues in Islamic history and it points out that reforms in women’s issues have more often than not been a State rather than a grassroots concern. The strength of the introduction is that in contrast to many of the other articles in this volume, it takes into account not only the feminist point of view on gender but deals with the various views that exist in Muslim society. Haddad’s chapter introduces the first part of the anthology titled “Islam, Gender, and Social Change: A Reconstituted Tradition,” which gives the reader a short survey of the modem challenges facing Arab society. She sees the main factors of change in the Arab world as the economic fluctuations of the 1970s and 1980s: labor migration, women’s entrance into the labor market, State ideology and politics, the Islamic movement’s role in society, United Nations’ recommendations, and input from Western feminist movements. So far, so good; however, in her following comments, Haddad has a tendency to victimize Arab Muslim women, particularly the religious-oriented- viewpoint which, as a researcher on the Muslim world, I cannot always agree with. This victimization is partly a result of how Muslim women are often described from an outsider’s perspective, either from a Western or a secular Muslim point of view. Victimization of Muslim women is not only a feature in Haddad’s article but also in many of the other articles in this book. Interestingly, even the few Muslim contributors do not have a particular Islamic outlook; rather, they are part of a Western research paradigm. The fact that Islamic-oriented Muslim women are generally defined within a frame of Western research traditions reinforces, on the one hand, attitudes of “we” and “them” and, on the other, the notion that these women are victims rather than women responsible for their own lives ...